Efficiency in Business and Economics Proceedings from the 7th International Conference on Efficiency as a Source of the Wealth of Nations (ESWN), Wrocław 2017 (Springer Proceedings in Business and Economics,, 2018)
This volume offers a collection of studies on problem of organization's efficiency, criteria for evaluating the efficiency, tools and methods for measuring the efficiency. The articles included present an interdisciplinary look at efficiency, its essence and the principles of its measurement. The contributions also identify a broad spectrum of conditions for achieving efficiency in various types of organizations and systems (e.g. public institution, non-profit organizations), representing various industries. The book collects selected papers presented at the 7th International Conference "Efficiency as a Source of the Wealth of Nations", held in Wrocław, Poland, in May 2017. .